Specchiate sembianze Studi di letteratura sarda - Pirodda, Giovanni (La biblioteca di Medea, 2022)
In the field of Sardinian literature, the volume collects the best of Giovanni Pirodda's articles and shows his rare ability to combine a synthetic overview - capable of bold diachronic weavings from which crucial literary facts emerge, in the constant tension between canon and deviation from it - with the author's portrait and the precise analysis of his texts. Pirodda's reflections have unquestionably qualified the critical vicissitudes of the leading figures in contemporary Sardinian literature, such as Grazia Deledda, Antioco Casula, Giuseppe Dessì and Salvatore Satta.